EFFECT OF CORPORATE IMAGE AND QUALITY SERVICE LOYALTY THROUGH CUSTOMER SATISFACTION NATURAL IMAGE HOTEL DEMAK (Students' Journal of Economic and Management, 2013)
The purpose of this study is to demonstrate the influence of corporate image and service quality on loyalty through customer satisfaction. To examine this research is necessary to study the theory of the meaning of corporate image understanding, understanding service quality, loyalty and sense of understanding consumer satisfaction. Using quantitative research approaches to test the inferential process is to test the hypothesis proposed in theory. Sampling technique is done using purposive random sampling, where sampling with particular consideration. The sample in this study amounted to 95 users hotels Citra Alam Demak. Data collection techniques using primary data in the form of a questionnaire. Then the data analysis tools using multiple regression and simple regression whereas hypothesis testing using t-test. The results showed that (1) the company's image significantly influence consumer satisfaction, influence the value of 18.14%, (2) the quality of services significantly influence customer satisfaction, influence the value of 24.20% and (3) significantly influence consumer satisfaction consumer loyalty, pengarunya value of 58.21%. Then the value of the adjusted coefficient of determination (adjusted R ²) variable corporate image and service quality variables can explain konusmen satisfaction of 0.688 or 68.8%. Then the coefficient of determination (adjusted R2) of customer satisfaction on loyalty of 0.577 or 57.7% were able to explain variation in customer satisfaction loyalty variableKeywords: Corporate Image, Service Quality, Satisfaction and Loyalty